Environmental art a basic introduction - Alipon, Aileen Escueta; Mayo, Adelaida Villaraza (1995.)
A basic introduction to Environmental Art which stresses on the importance of the consciousness of this art form in executing "thoughtful designs". It focuses on the application of Environmental Art on interiors; how it can put more thought into designs and on a more socio-political level, address such concerns. Interiors from Show House 2, featuring interiors with AIDS as an underlying theme, and Mr. Junie Rodriguez's personal space, are documented to display the so-called "thoughtful designs" in the best possible way. Selected works of the artist Christo are likewise presented to show Environmental Art using a different approach. Although this paper is not a how-to instructional material, is is hoped that though this, the awareness and consciousness of this art form will be awakened so that we will have a better understanding of what we are doing, what we intend to do, and what it can do in return. Consequently, we will be able to design spaces that have more thought and character.
Thesis(BID)--University of the Philippines Diliman.
Keywords: Art -- Environmental aspects--Philippines.; Interior decoration